The 2nd Guards Tank Army in the Berlin Strategic Offensive Operation - V. O. Daynes (Vestnik MGIMO-Universiteta)
One of the greatest battles of the Great Patriotic and also the World War II took place on the outskirts of the capital of Nazi Germany on April 16, 1945. Three magor fronts - 1st Belorussian, 2nd Byelorussian, 1st Ukrainian - and four tank armies were involved. They were not used as highly mobile groups to enter Berlin from the north and north-west, they were sent first to break powerful enemy defenses, and then to wage battles on the streets. The Supreme Command and the commanders of the 1st Byelorussian and 1st Ukrainian fronts understood the inevitability of heavy losses in tanks and troops, but deliberately took this step. The aim was not only a speedy capture of the German capital and the end of the war, but also to be ahead of allies on their way to Berlin. The article deals with the planning and preparation for the Berlin Strategic Offensive Operation, the use of 2nd Guards Tank Army, who played along with other tank divisions a magor role in the success of this operation.